Context input process product evaluation of hybrid learning practices in Indonesian universities - Adi Suryanto; Aman Aman; Lia Yuliana; Nurtanio Agus Purwanto; Fery Muhamad Firdaus; Rahmat Fadhli (International Journal of Evaluation and Research in Education (IJERE), 2024)
The transformation of post-pandemic learning at Indonesian universities is becoming increasingly diverse. Several universities use hybrid learning models to implement hybrid learning practices. The purpose of this study is to assess the hybrid learning process at two Indonesian universities. The context input process product (CIPP) evaluation model is used in this study as part of a mixed method. Quantitative methods are used to get an overview of student and lecturer responses, whereas qualitative methods are used to dig deeper into data about hybrid learning practices. This study included 341 students and 22 lecturers from both universities. Techniques for collecting data include questionnaires, interviews, observation, and documentation studies. The data was analyzed using learning theories. The study’s findings indicate that hybrid learning practices are performing well. The readiness of university infrastructure, as well as the readiness of students and lecturers, determines the success of hybrid learning implementation. In practice, however, some lecturers tend to use face-to-face or online learning practices exclusively to fill gaps in the hybrid learning process. This study suggests that universities investigate an effective model for implementing hybrid learning.